Cardiorespiratory fitness measured with cardiopulmonary exercise testing and mortality in patients with cardiovascular disease: A systematic review and meta-analysis - Ezzatvar, Yasmin; Izquierdo, Mikel; Núñez, Julio; Calatayud, Joaquín; Ramírez-Vélez, Robinson; García-Hermoso, Antonio (Journal of sport and health science, 2021)
•High cardiorespiratory fitness (CRF) in patients with cardiovascular disease (CVD) is associated with 58% lower all-cause mortality risk and 73% lower cardiovascular mortality risk compared to unfit counterparts.•Each 1 metabolic equivalent (1-MET) increase in CRF is associated with a 19% lower CVD mortality risk among patients with CVD.•Coronary artery disease patients with high CRF have a 68% lower all-cause mortality risk than their unfit counterparts.•Each 1-MET increase in CRF is associated with a 17% lower all-cause mortality risk among patients with coronary artery disease.•No significant associations were found between increments of 1-MET and lower mortality risk among heart failure patients. Cardiorespiratory fitness (CRF) is inversely associated with mortality in apparently healthy subjects and in some clinical populations, but evidence for the association between CRF and all-cause and/or cardiovascular disease (CVD) mortality in patients with established CVD is lacking. This study aimed to quantify this association. We searched for prospective cohort studies that measured CRF with cardiopulmonary exercise testing in patients with CVD and that examined all-cause and CVD mortality with at least 6 months of follow-up. Pooled hazard ratios (HRs) were calculated using random-effect inverse-variance analyses. Data were obtained from 21 studies and included 159,352 patients diagnosed with CVD (38.1% female). Pooled HRs for all-cause and CVD mortality comparing the highest vs. lowest category of CRF were 0.42 (95% confidence interval (95%CI): 0.28–0.61) and 0.27 (95%CI: 0.16–0.48), respectively. Pooled HRs per 1 metabolic equivalent (1-MET) increment were significant for all-cause mortality (HR = 0.81; 95%CI: 0.74–0.88) but not for CVD mortality (HR = 0.75; 95%CI: 0.48–1.18). Coronary artery disease patients with high CRF had a lower risk of all-cause mortality (HR = 0.32; 95%CI: 0.26–0.41) than did their unfit counterparts. Each 1-MET increase was associated with lower all-cause mortality risk among coronary artery disease patients (HR = 0.83; 95%CI: 0.76–0.91) but not lower among those with heart failure (HR = 0.69; 95%CI: 0.36–1.32). A better CRF was associated with lower risk of all-cause mortality and CVD. This study supports the use of CRF as a powerful predictor of mortality in this population. [Display omitted]